Fabrication and Ablation Studies of 4D C/SiC Composite Nozzle Under Liquid Propulsion. (24th February 2015) - Kumar, Suresh; Kumar, Anil; Mala, Ramesh Babu; Mokhasunavisu, Raghvendra Rao
Abstract : 4D C/SiC composite nozzle was fabricated using LSI and characterized for mechanical, thermal, and ablation properties. Average flexural and compressive strengths in the Z‐direction were found to be 119 and 110 MPa, while in the U‐, V‐ and W‐directions, they were 99 and 55MPa, respectively. Coefficient of thermal expansion was found to be varied in the range 0–1.5 × 10 −6 /°C (25–1050°C), while thermal diffusivity was 40–5 mm 2 /s (25–1200°C). Ablation behavior of the nozzle was evaluated under UH25/N2 O4 propulsion system for 30 s. The overall mass erosion rate and the linear ablation rate were found to be 0.119 kg/m 2 s and 0.05 mm/s, respectively.